Tandem non-polymerizing strategy to higher order acrylamide oligomers; potential intermediates for conformational correlations of poly-N-acrylamides - Kendhale, Amol M.; Rajamohanan, Pattuparampil R.; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2008)
This letter describes an efficient tandem non-polymerization strategy to deliver higher order N-acrylamide oligomers. These oligomers, accessible in an one-pot procedure, are potential intermediates for the correlation of stereochemistry (tacticity) with conformation and hydrogen bonding propensities in poly (oligo) N-acrylamides.

Three in one: prototropy-free highly stable AADD-type self-complementary quadruple hydrogen-bonded molecular duplexes with built-in fluorophore - Kheria, Sanjeev; Rayavarapu, Suresh; Kotmale, Amol S.; Sanjayan, Gangadhar J. (Chemical Communications, 2017)
This communication reports an effective approach for addressing the prototropy-related problems in heterocycle-based AADD-type self-assembling systems by freezing their hydrogen-bonding codes, by utilizing intramolecular bifurcated hydrogen bonding interactions. Using this strategy, we have also developed a hydroquinone-conjugated AADD-type self-assembling system adorned with three valuable features such as prototropy-free dimerization yielding single duplexes, high duplex stability and a built-in fluorophore, which would augment its application potential. The rational approach used herein to arrest prototropic shift may also find application elsewhere, wherein proton shift-mediated structural changes become a detrimental factor.

Triazine-based highly stable AADD-type self-complementary quadruple hydrogen-bonded systems devoid of prototropy - Kheria, Sanjeev; Rayavarapu, Suresh; Kotmale, Amol S.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (Chemistry-A European Journal, 2017)
A new class of 1,3,5-triazine-based quadruple hydrogen-bonded system featuring AADD-type self-complementary arrays has been developed and characterized. This system forms highly stable molecular duplex in non-polar solvent (K-dim > 1.9 x 10(7) M-1 in CDCl3) without prototropy-related issues, raising its prospects for application in supramolecular polymer science.

Three-dimensional metal-organic polymer of multivalent hexaphenylbenzene - Madhu, Suresh; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (ChemistrySelect, 2018)
Metal-Organic Frameworks(MOFs) synthesized from ligands more than ten co-ordinating sites may offer material applications due to their structural architecture. Herein, a synthesis of metal-organic framework is reported from a ligand featuring 12-aryl carboxylic acid groups appended on a hexaphenylbenzene and s-block element potassium. The synthesized MOF was characterized by thermogravimetric analysis, infrared spectroscopy and X-diffraction studies. The X-ray crystal structure of MOF was shown to have a significant number of trapped and coordinated water molecules in its three-dimensional framework.

Twelve-armed hexaphenylbenzene-based giant supramolecular framework for entrapping guest molecules - Madhu, Suresh; Gonnade, Rajesh G.; Das, Tamal; Vanka, Kumar; Sanjayan, Gangadhar J. (ChemPlusChem, 2018)
Host-guest chemistry is a functional model in supramolecular chemistry for understanding specific process occurring in biological systems. Herein, we describe a rationally designed giant multiarmed hexaphenylbenzene (HPB)-based supramolecular frameworks which encapsulate a variety of guest molecules in the voids of their crystal lattice through the cooperative interplay of multivalency, noncovalent forces and backbone rigidity. In this connection, pseudo-axially substituted twelve-armed hexaphenylbenzene was synthesized and its molecular entrapping nature was studied by varying number of H-bond donor-acceptor sites in the arms. The per-methyl esterified HPB acted as a cavitand to include nonpolar and polar aprotic guests in its crystal structure via C-H center dot center dot center dot pi, C-H center dot center dot center dot O and C-H center dot center dot center dot N interactions. The corresponding amidated HPB showed unprecedented inclusion of ammonia and segregation of the guest molecules according to their polarity in the lattice. Furthermore, this molecular entrapping system has been used to obtain the crystal structure of a hitherto unproven 2-azaallenium intermediate, which had been proposed to be involved in aminomethylation of activated arenes.

Three in one: triple G-C-T base-coded brahma nucleobase amino acid: synthesis, peptide formation, and structural features - Wagh, Mahendra A.; Maity, Rahul; Bhosale, Rohit J.; Semwal, Divyam; Tothadi, Srinu; Vaidhyanathan, Ramanathan; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2021)
This note reports the synthesis and peptide formation of a novel triple G-C-T nucleobase amino acid (NBA) building block featuring three recognition faces: DDA (G mimic), DAA (C mimic), and ADA (T mimic). Readily obtainable in multigram scale in a remarkably easy one-step reaction, this unique NBA building block offers scope for wide ranging applications for nucleic acid recognition and nucleic acid peptide/protein interaction studies.

Triazine-based janus G-C nucleobase as a building block for self-assembly, peptide nucleic acids, and smart polymers - Meena, Chhuttan L.; Singh, Dharmendra; Kizhakeetil, Bhavya; Prasad, Manasa; George, Malini; Tothadi, Srinu; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2021)
This communication reports on the utility of a triazine-based self-assembling system, reminiscent of a Janus G-C nucleobase, as a building block for developing (1) supramolecular polymers, (2) peptide nucleic acids (PNAs), and (3) smart polymers. The strategically positioned self-complementary triple H-bonding arrays DDA and AAD facilitate efficient self-assembly, leading to a linear supramolecular polymer.

Triple G-C-T base-coded self-assembling water-soluble nucleobase monomers with a broad scope for biomaterial and protein bioconjugation applications - Singh, Dharmendra; Gone, Nilu V.; Bandi, Kiran; Davis, Disiya; Nair, Kiran Sukumaran; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2025)
We report self-assembling water-soluble nucleobase monomers with a broad scope for biomaterial and protein bioconjugation applications. These nucleobase monomers are adorned with nature-inspired triple G-C-T nucleobases featuring three recognition sites: DDA (G mimic), DAA (C mimic), and ADA (T mimic). Using readily accessible starting materials, these monomers can be synthesized in excellent yields, making them good choices for diverse applications. Their unique structural features, coupled with their water solubility, may offer exciting opportunities for the creation of new biomaterials.